Attitudes and Behaviors towards Online Financial Services via Smartphone of Thai Population in Bangkok, Thailand Metropolis and Vicinity during the Covid-19 Situation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This article aimed to study demographic factors, relationship between attitudes and behaviors towardsonline financial services via smartphones of Thai population in Bangkok, Thailand Metropolis andVicinity during the Covid-19 situation. The study was conducted among 400 Thai people living inBangkok, Thailand Metropolis and Vicinity. A questionnaire was used as the instrument. Statistics inthe study included percentage, mean, standard deviation, and Pearson correlation coefficient.The findings from the study showed that most of the participants were female school/collegestudents aged 18-25 years with an average monthly income of 5,000-10,000 baht and live in Bangkok.Most people knew how to use online financial services via smartphone through advertisements onsocial media such as Facebook, Twitter or Tiktok. They used the service of Siam Commercial Bank(SCB EASY APP) the most, 1-3 times /day. The type of transaction they most likely used was moneytransfer from their accounts to accounts of others. The reason they used the service was that it wasconvenient, fast and trendy. With regard to data analysis about attitudes and behaviors towards onlinefinancial services via smartphone of Thai population in Bangkok Metropolis and Vicinity during theCovid-19 situation, it was found that most people had attitudes towards “confidence in the bankingsystem” and most of them have behaviors towards online financial services via smartphone since itwas convenient, fast and easy to use.